Synthesis of 5‐substituted 1H‐tetrazoles and oxidation of sulfides by using boehmite nanoparticles/nickel‐curcumin as a robust and extremely efficient green nanocatalyst. (16th September 2020) - Jani, Muhammed Ali; Bahrami, Kiumars
Abstract : Nickel‐anchored curcumin‐functionalized boehmite nanoparticles (BNPs@Cur‐Ni) as a robust and versatile nanocatalyst was synthesized and well‐characterized by using Fourier transform infrared (FT‐IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X‐ray (EDX), X‐ray mapping, thermogravimetric analysis (TGA), differential thermal analysis (DTA), Brunauer–Emmett–Teller (BET), X‐ray diffraction (XRD), and inductively coupled plasma optical emission spectroscopy (ICP‐OES). The synthesis of 5‐substituted 1 H ‐tetrazoles and the oxidation of sulfides were conducted by BNPs@Cur‐Ni with excellent turnover number (TON) and turnover frequency (TOF) outcomes. Also, the catalyst was reused for several sequential runs without Ni leaching or decreasing in reaction yield. Utilizing the curcumin and boehmite with a natural source as well as poly(ethylene glycol) (PEG) as a solvent in this simple protocol can be based on green chemistry rules. Abstract : BNPs@Cur‐Ni is a new, green and very useful nanocatalyst made of cheap precursors materials that can be used to perform two significant reactions such as oxidation of sulfides and synthesis of tetrazoles with high efficiency